Reproductive systems in Paspalum : relevance for Germplasm collection and conservation, breeding techniques, and adoption of released cultivars - Acuña, Carlos Alberto (2019)
Fil: Acuña, Carlos Alberto. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.